PERSPECTIVE - Two lessons from the dolomites - Bosellini, Alfonso (Journal of Mediterranean Earth Sciences, 2014)
Taking into account two stratigraphic relationships of the Dolomites, two basic stratigraphic concepts are discussed. In the first case, it is shown that the principle of superposition must be applied with care, specially when large depositional systems are considered. In the second case, it is demonstrated the practical impossibility to apply Milankovitch cyclostratigraphy to shallow-water carbonate successions because it is impossibile to know the temporal length of hiatuses bounding the various cycles.